Layer deposition of titanium dioxide (TiO2) using DC-sputtering method with variation of deposition time: study of microstructure and coating hardness - Uli Aprilia Mukaromah; Wiwien Andriyanti; Heri Sutanto; Nuha Nazilah Sahabudin (Diponegoro University Semarang Indonesia, 2021)
The A thin layer of titanium dioxidehas been deposited using the DC-Sputtering method at various time of deposition of 30 minutes, 60 minutes, 90 minutes, 120 minutes and 150 minutes. This study aims to grow a layer of TiO2 on the surface of stainless steel 316L with a certain time variation to determine the characterization of the microstructure, hardness, and properties of the coating to the water contact angle. The XRD test results show that the titanium dioxide (TiO2) thin layer has a TiO2-monoclinicstructure corresponding to the planes (133), (133), (220), (133) and (133), while the crystallite size can be determined using Debye-scherrer Equation were 14.34318 nm, 17.09422 nm, 18.94568 nm, 14.04389 nm, and 7.90887 nm, respectively. The hardness value was obtained through the Vickers Hardness Test and it is known that the TiO2 layer can increase the hardness value by 48.175% with a maximum hardness value of 170.105 VHN at a deposition time of 90 minutes. Observations from the contact angle test can be seen that the TiO2 layer is hydrophilic.